Vitte, a gazdaságpolitikus: WITTE, THE ECONOMIC POLITICIAN - Bebesi, György (Közép-Európai Közlemények, 2020)
The article presents the perception of Sergei Yulevich Witte, an outstanding Russian statesman at the turn of the nineteenth and twentieth centuries, on the current state of the Russian economy and industry, and focuses on several important features from his practical economic performance that determined the economic policy of that period. Among these, it analyses the circumstances of the introduction of the gold ruble, the customs war with Germany, and the reforms that have been implemented in the area of alcohol distribution, and by presenting these, it seeks to highlight the prominent role of the politician in Russian history.